On the Bound of the C* Exponential Length. Issue 4 (1st December 2014) - Pan, Qingfei; Wang, Kun
Abstract: Let X be a compact Hausdorff space. In this paper, we give an example to show that there is u C( X ) M_n with ( u( x ) ) = 1 for all x X and u _h1 such that the C^* exponential length of u (denoted by cel( u ) ) cannot be controlled by π . Moreover, in simple inductive limit C^* -algebras, similar examples also exist.